Assessment of value of protraction angle and functional disorders of motion segments of cervical spine in bus drivers - Aleksandra Madej; Zbigniew Śliwiński; Żaneta Wypych; Arkadiusz Żurawski (Kazimierz Wielki University, 2022)
Introduction: Cervical segment is a part of the spine which is the most exposed to stress and dysfunction. Aim: The aim of the study is to analyze the body posture of bus drivers and, especially, functional assessment of cervical spine mobility segments. Material and methods: The study included a group of 40 people, consisting of professionally active drivers working in public transport, 20 of whom were the men under 40, and the remaining 20 were the men over 40. The study used the original study card. Results: There was dependence between the subjects' length of service and the appearance of hand numbness. There was dependence between protraction angle and length of service. Most of the study subjects (67.5%) report the presence of back pain syndromes. Among the study subjects, 45.0% declare that they do sports / physical activity improving their condition. In the case of rectus abdominis muscle strength, the majority of the surveyed (60.0%) cannot sit unassisted. Conclusions: The bus driver is exposed to a lot of stress every day, resulting, i.a. from the responsibility he bears for passengers in the vehicle, as well as from heavy traffic, which leads to changes in myofascial tensioning, resulting in the incidence of pain.